A network meta-analysis and systematic review of change in QRS duration after left bundle branch pacing, His bundle pacing, biventricular pacing, or right ventricular pacing in patients requiring permanent pacemaker - Tokavanich, Nithi; Prasitlumkum, Narut; Mongkonsritragoon, Wimwipa; Cheungpasitporn, Wisit; Thongprayoon, Charat; Vallabhajosyula, Saraschandra; Chokesuwattanaskul, Ronpichai (Scientific reports, 2021)
Cardiac dyssynchrony is the proposed mechanism for pacemaker-induced cardiomyopathy, which can be prevented by biventricular pacing. Left bundle branch pacing and His bundle pacing are novel interventions that imitate the natural conduction of the heart with, theoretically, less interventricular dyssynchrony. One of the surrogate markers of interventricular synchrony is QRS duration. Our study aimed to compare the change of QRS duration before and after implantation between types of cardiac implantable electronic devices (CIEDs): left bundle branch pacing versus His bundle pacing versus biventricular pacing and conventional right ventricular pacing. A literature search for studies that reported an interval change of QRS duration after CIED implantation was conducted utilizing the MEDLINE, EMBASE, and Cochrane databases. All relevant works from database inception through November 2020 were included in this analysis. A random-effects model, Bayesian network meta-analysis was used to analyze QRS duration changes (eg, electrical cardiac synchronization) across different CIED implantations. The mean study sample size, from 14 included studies, was 185 subjects. The search found 707 articles. After exclusions, 14 articles remained with 2,054 patients. The His bundle pacing intervention resulted in the most dramatic decline in QRS duration (mean difference, − 53 ms; 95% CI − 67, − 39), followed by left bundle branch pacing (mean difference, − 46 ms; 95% CI − 60, − 33), and biventricular pacing (mean difference, − 19 ms; 95% CI − 37, − 1.8), when compared to conventional right ventricle apical pacing. When compared between LBBP and HBP, showed no statistically significant wider QRS duration in LBBP with mean different 6.5 ms. (95% CI − 6.7, 21). Our network meta-analysis found that physiologic pacing has the greatest effect on QRS duration after implantation. Thus, HBP and LBBP showed no significant difference between QRS duration after implantation. Physiologic pacing interventions result in improved electrocardiography markers of cardiac synchrony, narrower QRS duration, and might lower electromechanical dyssynchrony.